2014
DOI: 10.1089/dia.2013.0278
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Feasibility and Impact of an Internet-Based Lifestyle Management Program in a Diabetes Care Setting

Abstract: This before-after pilot study demonstrates that adding an Internet-based lifestyle modification program to usual care may improve clinically important outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…The number of internet-based approaches for lifestyle changes in self-management programs has increased in several settings, both in adolescents and in adults, [25][26][27] and in different non-communicable diseases. [28][29][30][31][32] The most recent approaches allow for interaction with therapists, and also with peers in discrete groups, while maintaining privacy. Accordingly, they tend to overcome the drawbacks of classical approaches, based on face-to-face or group-based meetings with counselors, reaching the limited audience able to attend the clinic during working hours, in countries where treatment is regulated by a universal healthcare system, or are able to pay for private treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The number of internet-based approaches for lifestyle changes in self-management programs has increased in several settings, both in adolescents and in adults, [25][26][27] and in different non-communicable diseases. [28][29][30][31][32] The most recent approaches allow for interaction with therapists, and also with peers in discrete groups, while maintaining privacy. Accordingly, they tend to overcome the drawbacks of classical approaches, based on face-to-face or group-based meetings with counselors, reaching the limited audience able to attend the clinic during working hours, in countries where treatment is regulated by a universal healthcare system, or are able to pay for private treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In a multiple regression analysis, Chin et al 30 reported that increased frequencies of logging weight, exercise, breakfast, and dinner were all positively associated with a 9-month weight loss (controlling for age, gender, and baseline BMI). In a multiple regression analysis, Sherifali et al 31 reported non-significant effects of website login frequency and lesson unit completion on a 1-year weight loss (controlling for age and gender). Finally, in a structural equation analysis, Kim et al 32 reported that increased group participation and food logging frequency were predicted in a 6-month weight loss.…”
Section: Discussionmentioning
confidence: 99%
“…By comparison, we can see that virtually all patients evolved to a better condition, but six months is insufficient to achieve the ADA goals (HbA1c: 7%; preprandial plasma glucose: 70-130 mg/dl; postprandial plasma glucose: less than 180 mg/dl). With the advancement of science and technology, a step forward would be enough to harness the Internet to allow patients to selfmonitor and keep updated through the website of the health institutions, as has already been experienced (16).…”
Section: Discussionmentioning
confidence: 99%